A DETAILED X-RAY INVESTIGATION OF ζ Puppis. II. THE VARIABILITY ON SHORT AND LONG TIMESCALES - Nazé, Yaël; Oskinova, Lidia M.; Gosset, Eric (The Astrophysical journal, 2013)
Stellar winds are a crucial component of massive stars, but their exact properties still remain uncertain. To shed some light on this subject, we have analyzed an exceptional set of X-ray observations of ζ Puppis, one of the closest and brightest massive stars. The sensitive light curves that were derived reveal two major results. On the one hand, a slow modulation of the X-ray flux (with a relative amplitude of up to 15% over 16 hr in the 0.3-4.0 keV band) is detected. Its characteristic timescale cannot be determined with precision, but amounts from one to several days. It could be related to corotating interaction regions, known to exist in ζ Puppis from UV observations. Hour-long changes, linked to flares or to the pulsation activity, are not observed in the last decade covered by the XMM observations; the 17 hr tentative period, previously reported in a ROSAT analysis, is not confirmed either and is thus transient, at best. On the other hand, short-term changes are surprisingly small (<1% relative amplitude for the total energy band). In fact, they are compatible solely with the presence of Poisson noise in the data. This surprisingly low level of short-term variability, in view of the embedded wind-shock origin, requires a very high fragmentation of the stellar wind, for both absorbing and emitting features (>10[SUP]5[/SUP] parcels, comparing with a two-dimensional wind model). This is the first time that constraints have been placed on the number of clumps in an O-type star wind and from X-ray observations. Based on observations collected with XMM-Newton, an ESA Science Mission with instruments and contributions directly funded by ESA Member States and the USA (NASA).